Barriers to the Production of Scientific Dental Articles in Dental Schools in Iran; the View of Postgraduate Students - Hadi Ghasemi; Mohammad Reza Khami (Tehran University of Medical Sciences, 2012)
Background and Aims: The present study aimed to evaluate the barriers to the production of scientific dental articles in dental schools in Iran based on the opinions of dental postgraduate students.Materials and Methods: A self-administered questionnaire was distributed among postgraduate students of all Iranian dental schools in June 2010. The respondents rated their agreement with eight sentences about what hinder them from producing scientific dental articles based on a 5-grade Likert scale. The data were analyzed usingChi-square test.Results: Totally, 270 filled questionnaires from 14 dental schools were received. Of all respondents, 53% were male, the mean age were 29.6 ± 3.8. About half of the respondents reported at least one published article. Less than half of the respondents reported producing an article from undergraduate thesis; more women than men and more younger than older students (P<0.03). About two-third of the respondents rated absence of an English editing center, no financial incentives, no appropriate environment, and no competency for scientific writing as most prevalent barriers to the production of scientific dental articles.Conclusion: To expand the share of Iran in the production of scientific dental documents, the potential of postgraduate dental students must be regarded and suitable condition for scientific writing must be provided. Specifically, based on the findings of the present study, provision of an English editing facility, establishing financial incentives, and providing the students with appropriate environment and efficient scientific writing education are of utmost importance.